Strengthening Higher Education in Laos - Knight, Jane (International Higher Education, 2013)
Internationalization plays a critical role in building university capacity, especially in developing countries. In the current world of higher education-with competitiveness, branding, and commercialization front and center-inter- national development cooperation is often relegated to a low priority. Status building networks with elite partners are receiving more attention and support than capacity- building initiatives with developing country institutions.